Growth performance of olive barb Puntius sarana (Hamilton, 1822) in response to use of different supplementary feeds during high density rearing of spawn to fry stage - Das, P. C.; Jena, J. K.; Patro, Babita; Mishra, Sudhansu Shekhar (Indian Journal of Fisheries, 2016)
Rearing of olive barb spawn at high stocking density (2400 m-2) was carried out for one month in large concrete seed rearing tanks having soil base. The spawn were fed with three feed combinations (treatments) namely, T1: groundnut oil cake + rice bran at 1:1, T2 : ground nut oil cake + rice bran + fish meal at 40:40:20 and T3 : Soyamilk + egg custard. After 30 days rearing, T2 showed approximately 20% higher survival than T1 (50.5±1.9%), whereas the survival was significantly lower in T3 (43.2±5.2%). In T2, the fry showed a clear edge in growth within 10 days of rearing, which continued further to register 24 and 47.3% higher weight over T1 and T3 respectively, after 30 days. Higher survival, final body weight as well as biomass yield in T2 over T1 revealed requirement of additional animal protein (fish meal) in the diet for better nourishment of olive barb in nursery phase. But in T3, despite presence of soybean and egg protein, fry showed poor survival (43%) and growth, indicating unsuitable or inadequate nutrient supplementation through this diet as compared to the other two.